Enhancing Students’ Scientific Communication Skills in Electrochemistry through an Ethno-STEM–Based POE2WE Model - Defliani Adam; Masrid Pikoli; Julhim S. Tangio; Wiwin Rewini Kunusa; Erga Kurniawati; Thayban Thayban (Jambura Journal of Educational Chemistry, 2026)
Students' scientific communication skills in electrochemistry have not developed optimally because learning tends to emphasize cognitive aspects. This study aims to examine the effect of applying the Prediction, Observation, Explanation, Elaboration, Write, and Evaluation (POE2WE) learning model based on Ethno-STEM on scientific communication skills in electrochemistry. This study used a quasi-experimental method with a nonequivalent control group design involving 62 students from Suwawa 1 Public High School who were divided into an experimental group and a control group. The research instruments consisted of a test in the form of seven essay questions and non-test instruments to assess scientific communication skills during the learning process. The Mann-Whitney test results showed an Asymp. Sig. (2-tailed) value < 0.001, indicating a significant effect of the application of the Ethno-STEM-based POE2WE learning model on students' scientific communication skills. Based on the N-Gain calculation results, the scientific writing indicator was in the high category, while the information representation indicator was in the moderate category in the experimental group. In addition, the non-test assessment results showed an increase in students' scientific communication skills in three of the four indicators observed in each learning meeting.